Education and Social Change in Spain: from Crisis to Opportunity - Rivas-Flores, José Ignacio; Cortés-González, Pablo; Leite-Méndez, Analía Elizabeth (My University, 2014)
The current situation of crisis in Spain is bringing a new model of educational system justified on competitive and economistic grounds. New regulations, such as the LOMCE (Organic Law of Education), put emphasis in the privatization of social institutions at the expense of a pedagogical and democratic perspective. Nowadays a lot of students and families are suffering those all political and economic decisions. For example, according to UNICEF new statistics in Spain have reached into 26, 7% of children poverty. However, there are many groups that are working for the construction to another reality around the Spanish territory. In this symposium I am going to present an ethnographical research that shows an experience of resistance in Malaga city. Schools, associations and other collectives are working together in order to support and generate new educational practises based on the solidarity, dignity and justice. References: Cortes-Gonzalez, P. (2013). El guiño del poder, la sonrisa del cambio. Estudio pedagógico sobre identidad resiliente en situaciones de desventaja social, cultura y jurídica. Universidad de Málaga.
Keywords: Educación; Crisis económicas; Etnografía educativa; Educacion social; Marginalidad